Optimasi Performansi Sistem Kontrol Prosthesis Lengan Dengan Menggunakan Metode PID Tuning Dengan MATLAB - Prasad, Karuna Sindhu Krishna; Fauzi, Ilham; Adiputra, I.M.E. Darmayasa; Winata, I.M.P. Arya; Widhiada, I.W. (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2023)
The arm prosthesis in this study will analyze the control system of one finger with 3 joints, the aim is to determine the optimal performance of the control system for the prosthesis using 3 combinations of software, namely autodesk fusion 360, autodesk inventor as the design of the arm prosthesis, and matlab simulink simscape multibody as a simulation of PID tuning with a value of 4.0715 for proportional (P), 99.3021 for integral (I), and 0.039866 for (D) resulting in a movement performance with a rise time of 0.00431 seconds, settling time of 0.026 seconds, and overshoot of 4.76%.